(untitled) (Journal of Social Sciences Review, 2025)
Learner engagement and motivation play an important role in learning a second or foreign language. This study examines the effect of teacher talk on the two psychological constructs in Pakistani ESL classrooms. It evaluates teachers’ strategies to engage learners in instructional tasks and materials during classroom discourse. Using Flanders’ Interaction Analysis Categories (FIAC) as a theoretical framework, the research adopts a mixed-methods approach to analyze teacher-student interactions. Twenty-five undergraduate students and two teachers from a local college in Lahore, Punjab, participated in the study. Data collected through classroom observations, video recordings, and field notes revealed that inclusive questioning, positive reinforcement, and effective use of paralinguistic features significantly enhance learner engagement and motivation. The study offers valuable insights into effective strategies for fostering teacher-student relationships, thereby enhancing learner engagement and L2 motivation, by examining the diverse types of teacher talk. Additionally, the study focuses on the attitudes of academically struggling students during teacher talk. This study contributes significantly to the field by offering empirically grounded discourse strategies for language educators, extending Flanders’ framework to contemporary language classrooms. It particularly addresses the specific needs of academically low-performing learners and creates a methodological bridge between theoretical understanding and classroom practice.